Effect of benzyl alcohol and thiourea on electrodeposition of cadmium: electrochemical impedance spectroscopy study. (1st May 2013) - Vijayakumar, J; Mohan, S
<x xml:space="preserve">Abstract</x> The adsorption effect of the benzyl alcohol (BA) and thiourea (TU) on the electrodeposition of cadmium from an acid sulphate bath has been studied by electrochemical impedance spectroscopy (EIS). Maximum adsorption of additive was obtained in BA containing medium. Results show that the adsorption increases when the concentration of the additives is increased. The surface adsorption of the additives has lead to a decrease in the double layer capacitance and to an increase in polarisation resistance. The adsorption process is a spontaneous one and follows the Langmuir adsorption isotherm model. From the impedance analysis, it is observed that Cd-TU complexes inhibit the hexagonal like morphology revealed by SEM.